Letrozole, berberine, or their combination for anovulatory infertility in women with polycystic ovary syndrome: study design of a double-blind randomised controlled trial. Issue 11 (25th November 2013) - Li, Yan; Kuang, Hongying; Shen, Wenjuan; Ma, Hongli; Zhang, Yuehui; Stener-Victorin, Elisabet; Hung, Ernest; Ng, Yu; Liu, Jianping; Kuang, Haixue; Hou, Lihui; Wu, Xiaoke
Abstract : Introduction: Letrozole is being used as an alternative to clomiphene citrate in women with polycystic ovary syndrome (PCOS) requiring ovulation induction. Berberine, a major active component of Chinese herbal medicine rhizoma coptidis, has been used to improve insulin resistance to facilitate ovulation induction in women with PCOS but there is no study reporting the live birth or its potential as a complementary treatment to letrozole. We aim to determine the efficacy of letrozole with or without berberine in achieving live births among 660 infertile women with PCOS in Mainland China. Methods and analysis: This study is a multicentre randomised, double-blind trial. The randomisation scheme is coordinated through the central mechanism and stratified by the participating site. Participants are randomised into one of the three treatment arms: (1) letrozole and berberine, (2) letrozole and berberine placebo, or (3) letrozole placebo and berberine. Berberine is administered three times a day (1.5 g/day) for up to 24 weeks, starting on day 1 after a spontaneous period or a withdrawal bleeding. Either letrozole or letrozole placebo 2.5 mg is given daily from day 3 to day 7 of the first three cycles and the dose is increased to 5 mg/day in the last three cycles, if not pregnant. The primary hypothesis is that the combination of berberine and letrozole results in a significantly higher live birth rate than letrozole or berberine alone. Ethics and dissemination: The study was approved by the ethics committee of the First Affiliated Hospital of Heilongjiang University of Chinese Medicine. Study findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration: ClinicalTrials.gov identifier: NCT01116167 .